Suppression of Midgut Microbiota Impact Pyrethroid Susceptibility in Aedes aegypti - Gómez-Govea, Mayra A.; Ramírez-Ahuja, María de Lourdes; Contreras-Perera, Yamili; Jiménez-Camacho, Armando J.; Ruiz-Ayma, Gabriel; Villanueva-Segura, Olga Karina; Trujillo-Rodríguez, Gerardo de Jesús; Delgado-Enciso, Iván; Martínez-Fierro, Margarita L.; Manrique-Saide, Pablo; Puerta-Guardo, Henry; Flores-Suárez, Adriana E.; et al. (Frontiers in Microbiology, 2022)
Aedes aegypti is a mosquito that transmits viral diseases such as dengue, chikungunya, Zika, and yellow fever. The insect’s microbiota is recognized for regulating several biological processes, including digestion, metabolism, egg production, development, and immune response. However, the role of the bacteria involved in insecticide susceptibility has not been established. Therefore, the objective of this study was to characterize the resident microbiota in a field population of A. aegypti to evaluate its role associated with susceptibility to the insecticides permethrin and deltamethrin. Mosquitoes were fed 10% sucrose mixed with antibiotics and then exposed to insecticides using a diagnostic dose. DNA was extracted, and sequencing of bacterial 16S rRNA was carried out on Illumina® MiSeq™. Proteobacteria (92.4%) and Bacteroidetes (7.6%) were the phyla, which are most abundant in mosquitoes fed with sucrose 10%. After exposure to permethrin, the most abundant bacterial species were Pantoea agglomerans (38.4%) and Pseudomonas azotoformans-fluorescens-synxantha (14.2%). Elizabethkingia meningoseptica (38.4%) and Ps. azotoformans-fluorescens-synxantha (26.1%) were the most abundant after exposure to deltamethrin. Our results showed a decrease in mosquitoes’ survival when exposed to permethrin, while no difference in survival when exposed to deltamethrin when the microbiota was modified. We found that the change in microbiota modifies the response of mosquitoes to permethrin. These results are essential for a better understanding of mosquito physiology in response to insecticides.